A comparison of stimulus set size on tact training for children with autism spectrum disorder. Issue 1 (18th March 2019) - Kodak, Tiffany; Halbur, Mary; Bergmann, Samantha; Costello, Dayna R.; Benitez, Brittany; Olsen, Miranda; Gorgan, Ella; Cliett, Terra
Abstract : Previous studies on skill acquisition have taught targets in stimulus sets composed of different numbers of stimuli. Although the rationale for selection of a stimulus set size is not clear, the number of target stimuli trained within a set is a treatment decision for which there is limited empirical support. The current investigation compared the efficiency of tact training in 4 stimulus set sizes, each of which included 12 stimuli grouped into (a) 4 sets of 3 stimuli, (b) 3 sets of 4 stimuli, (c) 2 sets of 6 stimuli, and (d) 1 set of 12 stimuli. Results of all 4 participants with autism spectrum disorder show tact training with larger (i.e., 6 and 12) stimulus set sizes was more efficient than training with smaller (i.e., 3 and 4) stimulus set sizes.